THE DISTORTION OF GOVERNMENT BUREAUCRACY AND REGIONAL SELECTION - Akbar Maulana (Universitas Muhammadiyah Jember, 2021)
The problem of bureaucratic specialization in the implementation of regional elections as a form of the success of the government bureaucracy is often a problem. The process of implementing regional elections in several regions involving bureaucrats is still not maximal, so that many elected regional heads have not been able to carry out their duties to serve the community properly. On the other hand, bureaucrats must be neutral and supported by qualifications, scientific competence, and fair and reasonable performance without prioritizing political interests, so that their duties can be carried out rationally. The writing of this article was based on juridical aspects, namely Law Number 32 of 2004 concerning Regional Government and Regulation of the Minister of Home Affairs Number 9 of 2005 concerning Guidelines for Regional Government in the Implementation of Regional Head and Deputy Regional Head Elections. This writing intended to describe and analyze the neutrality attitude of government bureaucratic officials to the practice of Regional election power in Jember Regency. The writing method used a normative juridical approach with primary and secondary observation data collection techniques and document analysis. The conclusions of this study were: First, the neutrality of the government apparatus has not yet been carried out. Second, the problem of pressure from the writerities is still common. Third, there is no protection or no clear rules of the game from the involvement of the government bureaucracy in the regional election.